A pipeline for precise and efficient genome editing by sgRNA-Cas9 RNPs in Drosophila. Issue 1 (1st October 2020) - Nyberg, Kevin G.; Nguyen, Joseph Q.; Kwon, Yong-Jae; Blythe, Shelby; Beitel, Greg J.; Carthew, Richard
ABSTRACT: Genome editing via homology-directed repair (HDR) has made possible precise and deliberate modifications to gene sequences. CRISPR/Cas9-mediated HDR is the simplest means to carry this out. However, technical challenges remain to improve efficiency and broaden applicability to any genetic background of Drosophila melanogaster as well as to other Drosophila species. To address these issues, we developed a two-stage marker-assisted strategy in which embryos are injected with RNPs and pre-screened using T7EI. Using sgRNA in complex with recombinant Cas9 protein, we assayed each sgRNA for genome-cutting efficiency. We then conducted HDR using sgRNAs that efficiently cut target genes and the application of a transformation marker that generates RNAi against eyes absent . This allows for screening based on eye morphology rather than colour. These new tools can be used to make a single change or a series of allelic substitutions in a region of interest, or to create additional genetic tools such as balancer chromosomes.